2014
DOI: 10.1007/s11255-014-0743-9
|View full text |Cite
|
Sign up to set email alerts
|

Correlation study of chronic nonbacterial prostatitis with the levels of COX-2 and PGE2 in prostatic secretion

Abstract: Increase in PGE2 concentration caused by activated COX-2 pathway may contribute to the pain or discomfort symptom of the CNBP patients. Our results indicate that selective COX-2 inhibitors have application prospect in CNBP treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
2
0
3
Order By: Relevance
“…Studies have shown that the cause of the pain may be the inflammatory response caused by various factors that causes prostate tissue damage, which causes the prostate tissue to release some pain substances, such as β -endorphin ( β -EP), cyclooxygenase-2 (COX-2), and prostaglandin E2 (PGE2). These pain substances indirectly increase the excitability of nociceptors and sensitization of nociceptors by changing the endobiochemical microenvironment of the prostate [ 32 , 33 ]. Many studies have shown that the analgesic effect of acupuncture on CP/CPPS is closely related to the regulation of pain substances.…”
Section: The Mechanism Of Acupuncture and Moxibustion On Cp/cppsmentioning
confidence: 99%
“…Studies have shown that the cause of the pain may be the inflammatory response caused by various factors that causes prostate tissue damage, which causes the prostate tissue to release some pain substances, such as β -endorphin ( β -EP), cyclooxygenase-2 (COX-2), and prostaglandin E2 (PGE2). These pain substances indirectly increase the excitability of nociceptors and sensitization of nociceptors by changing the endobiochemical microenvironment of the prostate [ 32 , 33 ]. Many studies have shown that the analgesic effect of acupuncture on CP/CPPS is closely related to the regulation of pain substances.…”
Section: The Mechanism Of Acupuncture and Moxibustion On Cp/cppsmentioning
confidence: 99%
“…However, when cells are stimulated by pro-inflammatory cytokines or cancer-promoting factors, COX-2 shows upregulation and participates in inflammation as well as the formation and development of tumors [12,13]. Studies have shown that COX-2 is involved in CP [14,15], and inhibition of COX-2 suppresses the proliferation of prostatic epithelial cells in CNP [16]. MicroRNA (miRNA) is a class of endogenous non-coding small RNA with 19-25 nt in length, which is relatively conserved during evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Lokal olarak prostatta meydana gelen patoloji doku düzeyinde hassasiyet ve basınç oluşturmaktadır. Burada bahsedilen sitokinler ve kemokinler hücre sinyal molekülleridir ve gerek proinflamatuar, gerek inflamatuar gerekse de onarım sürecinde yer alan çok sayıda alt başlıkta incelenmektedir (45)(46)(47)(48)(49)(50). Bu hücre sinyalleri aracılığı ile lökositler artmakta ve ekstraprostatik sekresyonda (EPS) saptanmaktadır.…”
unclassified
“…KPAS'ta sıklıkla periferal zondan başlayarak periuretral alana ulaşan inflamasyon sonrası glanüler atrofi, stromal fibrozis sözkonusu olabilmektedir. Prostatta meydana gelen inflamasyona bağlı olarak COX-2 ve bunun neticesinde PGE2 artışı, mast hücre ve mast hücre ilişkili TRKA ve sonrasında NGF artışı, TRPV1 ve bununla ilişkili olarak SP, CGRP, PACAP artışları ağrı ile ilişkili mediatörlerdir (49)(50). PGE2 dokuda hipoksi, ödem ve ATP fonksiyon bozukluğu yapmaktadır (49).…”
unclassified
See 1 more Smart Citation